The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1143/jjap.46.l796
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Threshold Voltages of Nematic Liquid Crystal Electrooptical Devices by Doping Inorganic Nanoparticles

Abstract: We report the reduction of threshold voltage, V th , of twisted nematic liquid crystal devices by doping the nanoparticles of MgO and SiO 2 . The results are well explained by inserting the experimentally determined values of elastic constants and dielectric anisotropy in the formula, where both of these quantities decrease due to the existence of these nanoparticles. The V th decrease approximately as ffiffi ffi S p , where S being the order parameter. The S is also shown to decrease by doping nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 10 publications
3
63
0
2
Order By: Relevance
“…Fumiaki Haraguchi et al reported the reduction of threshold voltage of twisted nematic LC devices by doping the nanoparticles of MgO and SiO 2 [37]. The results were explained by inserting the experimentally determined values of elastic constants (k eff ) and dielectric anisotropy (Δε) in the formula Where elastic constant (k eff ) is directly proportional to the square of order parameter and dielectric anisotropy (Δε) is directly proportional to the order parameter.…”
Section: Properties Of Doped Nematic Liquid Crystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fumiaki Haraguchi et al reported the reduction of threshold voltage of twisted nematic LC devices by doping the nanoparticles of MgO and SiO 2 [37]. The results were explained by inserting the experimentally determined values of elastic constants (k eff ) and dielectric anisotropy (Δε) in the formula Where elastic constant (k eff ) is directly proportional to the square of order parameter and dielectric anisotropy (Δε) is directly proportional to the order parameter.…”
Section: Properties Of Doped Nematic Liquid Crystalsmentioning
confidence: 99%
“…Instead of synthesizing a large number of high quality LC compound, doping particles into LCs is a potentially cost effective way to attain these important feachures. The doping of nano particles into liquid crystal has emerged as a fascinating area of research to the application point of view [7][8][9][10]. Liquid crystal dispersions containing various types of nano particles have been developed in the recent years [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Допирование наночастицами Si 3 N 4 , ZnO, TiO 2 диаметром 25-35 нм понижало пороговое напряжение по сравнению с чистым ЖК, что объясняли захватом примеси ионов наночастицами за счет кулоновских сил [18]. Понижение порогового напряже-ния при добавлении наночастиц MgO и SiO 2 в твист-ячейках объясняли уменьшением упругих констант и диэлектрической анизотропии [19]. Таким образом, диэлектрические и упругие свойства легированного НЖК зависят от материала, структуры и концентрации наночастиц, а также их взаимодействия с молеку-лами и ионами примеси.…”
Section: Introductionunclassified
“…The properties of such materials, in most cases, significantly differ from those of the host materials. In the past few years there has been a significant increase in the number of published articles dealing with use of metallic, semiconducting, ferromagnetic or ferroelectric nanoparticles, fullerenes and carbon nanotubes in mixture with liquid crystals [1][2][3][4]. Depending on experimental parameters such as nanoparticle functionalization and concentration, size and core material, cell surface treatment, as well as applied electric or magnetic field diverse effects arise in different nematic liquid crystal hosts [4,5].…”
Section: Introductionmentioning
confidence: 99%